Exploring the Factors Influencing Consumer Reconsumption Intention of Herbal Medicine - Ahmed Bakhit, Mohammed Elfadil; Sudarto, Sudarto; Najmudin, Najmudin; Suliyanto, Suliyanto; Weni, Weni (The Es Economics and Entrepreneurship, 2025)
The research explores the factors of consumers’ trust in herbal medicine, perceived value, and the reconsumption intention that influence Indonesians to use herbal medicine for treatment and protection health conditions. This research uses consumer perceived value and relationship quality theory to explain research phenomena. The regression model was It employed a quantitative approach to determine the relationship of between consumers consumption behavior and herbal products. The sample in this study was selected using a purposive sampling. collected data by questionnaire. The results All proposed hypotheses are accepted, such as the effect of trust and perceived value on reconsumption intention. These results showed that consumer trust in the value and benefits of herbal medicine mediate the effect of perceived value on reconsumption intention. Therefore, there are still other factors included in this study related to consumers’ intention to (re)consume herbal medicine.